2020
DOI: 10.11591/ijere.v9i4.20670
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between preschool teachers’ self-efficacy beliefs and their teaching attitudes

Abstract: This study examined the relationship between preschool teachers’ selfefficacy beliefs and their teaching attitudes. In the study, it was considered whether preschool teachers’ self-efficacy beliefs and their teaching attitudes change in terms of certain variables. The research was carried out using a correlational survey model. The target population of the study is the preschool teachers working in Küçükçekmece district, İstanbul Province, in the 2017-2018 academic year. The working group consists of 264 presc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 13 publications
(12 reference statements)
0
8
0
Order By: Relevance
“…The correlation between self-efficacy and performance has been found to be positive in some studies [52,61,63] but non-significant in others [62,66]. The influence of teaching experience on this relationship remains ambiguous, with divergent findings in the literature.…”
Section: Hypothesis 5 (H5)mentioning
confidence: 99%
See 1 more Smart Citation
“…The correlation between self-efficacy and performance has been found to be positive in some studies [52,61,63] but non-significant in others [62,66]. The influence of teaching experience on this relationship remains ambiguous, with divergent findings in the literature.…”
Section: Hypothesis 5 (H5)mentioning
confidence: 99%
“…The multi-faceted nature of teacher efficacy, encompassing personal, outcome, and teaching efficacy, has been explored [51]. Furthermore, preschool teachers' self-efficacy beliefs positively correlate with their teaching attitudes [52], and completing a degree can enhance practicing teachers' self-efficacy [53].…”
Section: Theoretical Understandingmentioning
confidence: 99%
“…Teachers’ self-efficacy can be understood as the belief that teachers can influence students’ self-confidence to a certain extent ( Muijs and Reynolds, 2015 ). Some scholars have found that kindergarten teachers generally have sufficient self-efficacy beliefs, and this ability will affect the classrooms management, teaching process and communication skills of kindergarten teachers ( Kırkıç and Çetinkaya, 2020 ).…”
Section: Literature Review and Theoretical Hypothesesmentioning
confidence: 99%
“…Self-efficacy, as a predictor of cognitive participation ( Walker et al, 2006 ), has certain effects on teachers at all stages. For example, sufficient self-efficacy beliefs can have a certain planning and adjustment effect on the teaching process, communication skills and classroom management of kindergarten teachers ( Kırkıç and Çetinkaya, 2020 ). Emotional intelligence, as a non-cognitive affective factor, also plays an important role.…”
Section: Literature Review and Theoretical Hypothesesmentioning
confidence: 99%
“…Research infers that, the self-efficacy perceptions of preschool educators have many effects. It has been determined that there are significant relationships between preschool teachers' self-efficacy perceptions and classroom administration abilities (Bay, 2020;Semerci & Uyanık Balat, 2018), age, professional experience, and participation in activities such as seminars, conferences, congresses, courses, and symposiums (Koç & Sak, 2017), problem solving approach (Kesgin, 2006), and teaching attitudes (Kırkıç & Çetinkaya, 2020). When the studies conducted abroad on self-efficacy perceptions are examined, low self-efficacy beliefs of educators were associated with emotional exhaustion and depersonalization.…”
Section: Introductionmentioning
confidence: 99%